Establishment of a multifunctional impact system and a study of a pancreatic trauma model in rats based on controlling the injury area - Wang Hailin; Han Li; Zhao Zhirong; Wang Qingqing; Li Jingdong; Dai Ruiwu (Heliyon, 2023)
Background: At present, basic scientific research on pancreatic trauma is rare due to the lack of ideal animal models and modeling equipment for pancreatic trauma. Therefore, we intend to develop a multifunctional impact system with simple operation, diverse impact and accurate measurement and to establish a rat pancreatic trauma model based on injury area control by using the system. Methods: The impactor was designed based on the convenience of the impact energy acquisition, the diversity of the impact operation, and the precision of the impact strength parameter measurement by the team. The efficacy and stability/repeatability of the impactor were preliminarily evaluated. An impact head with different impact areas (3 cm2 and 6 cm2) of the impactor was used to squeeze the rat pancreas in the abdomen to form different injury areas under a pressure of 400 kPa. The efficacy features of this trauma model were evaluated by detecting the outcomes of pathology and biochemistry at 24 h after injury in the two groups. Furthermore, these changes were also evaluated at 6 h, 24 h, 48 h and 72 h after injury in the 3 cm2 trauma group. Result: Multifunctional impactors were successfully explored. The impact force was continuously adjustable with a range of 0–200 kg. The compression and extrusion stress ranges were continuously adjustable from 0 to 100 kg. System adjustment verified that the impactor had fine efficacy (P < 0.05) and stability/repeatability (P > 0.05). Compared with the control group, rats in the pancreatic trauma group with different injury areas exhibited obvious injuries (P < 0.05), and compared with the 3 cm2 trauma group, the 6 cm2 trauma group exhibited the more severe injury (P < 0.05). After modeling, the injury characteristics at different time points showed stable differences(P < 0.05). Conclusions: A rat pancreatic trauma model based on injury area control was successfully established using the impactor developed in this study. This model is simple, effective, controllable, and suitable for animal experimental research on pancreatic trauma.